Analysis of Financial Reporting Users: A Case Study on the Banking Restructuring Program - Imam Suprayogi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The preparation of financial reporting by an entity needs to consider the users of financial information because it is closely related to the purpose of preparing the financial statements. The law stipulates that the Indonesia Deposit Insurance Corporation must report the financial statements of the Banking Restructuring Program, but does not regulate how these financial statements should be presented. To determine the presentation of the financial statements, it is necessary to perform a user analysis of the financial statements. Using a qualitative case study approach, this research analyzes users and the financial information required from the Banking Restructuring Program. The results of the analysis show that the Banking Restructuring Program has various users of financial statements. Most of these users use the information in the financial statements to assess the accountability of the Banking Restructuring Program.